COMPUTATION OF INSECTS BIODIVERSITY IN BHENDI (ABELMOSCHUS ESCULENTUS (L.) MOENCH) ECOSYSTEM - CHAKRABORTY, ARDHENDU; K. KUMAR; N. CHITRA (The Bioscan, 2014)
Field experiments were conducted to inventorize the insect’s species in bhendi ecosystem. It was observed those hemipteran herbivores and hymenopteran and coleopteran predators were relatively abundant in kharif, 2012 and rabi, 2012-13 respectively. It was found that the herbivores (77.23 and 74.83 per cent) were relatively abundant followed by predators (22.77 and 25.17 per cent). The species richness (R) of predators (3.08 and 2.95) was more than herbivores (2.62 and 2.67) and a decreasing trend of evenness (J) was observed in predators. The Shannon and Wiener diversity index (H’) and Simpson index (λ) values of herbivores (2.286 and 2.294) (0.155 and 0.154) and predators (2.882 and 2.757) (0.063 and 0.076) were more or less same. The species diversity indices and species evenness indices of predators and herbivores were more or less equal and exhibited a similar diversification in kharif and rabi season. The biodiversity indices in bhendi was not reported earlier and henceforth the present findings stand as a base for further research in the biodiversity of arthropods in bhendi ecosystem.